Sistem Informasi Absensi Pegawai Berbasis Web di Kantor Desa Nagreg - Utami Aryanti; Sinta Karmila (INTERNAL (Information System Journal), 2022)
Employee attendance very influential on work productivity in achieving company goals, especially in government agencies related to community services as an indicator in employee performance appraisal. The attendance process at the Nagreg Village office as one of the government agencies is still done manually so that data collection on attendance hours, outgoing hours, recapitulation of employee attendance requires a relatively long time in the calculation and search process. An attendance information system is needed to overcome these problems. Attendance Information System in this study was built using the waterfall method which consists of the stages of analysis, design, coding, and testing. UML (Unified Model Language) is also used as a modeling tool in the analysis and system design stages